2020
DOI: 10.1111/1744-7917.12791
|View full text |Cite
|
Sign up to set email alerts
|

Insect group II chitinase OfChtII promotes chitin degradation during larva–pupa molting

Abstract: The insect group II chitinase (ChtII, also known as Cht10) is a unique chitinase with multiple catalytic and chitin-binding domains. It has been proven genetically to be an essential chitinase for molting. However, ChtII's role in chitin degradation during insect development remains poorly understood. Obtaining this knowledge is the key to fully understanding the chitin degradation system in insects. Here, we investigated the role of OfChtII during the molting of Ostrinia furnacalis, a model lepidopteran pest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…Functional annotation of the pink, magenta and salmon modules indicated that enriched GO terms and KEGG pathways were significantly associated with metabolism, coinciding with rapid metamorphic development during these stages. For instance, the enrichment of chitin metabolic processes and chitin binding are closely related to the formation and degradation of chitin, which is a major structural component of the insect cuticle that protects insects from chemical erosion, physical abrasion and pathogenic invasion [ 53 , 54 ] and serves as an attachment matrix for other cuticular proteins, plays an important role in molting during the larval-larval and larval-pupal stages [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional annotation of the pink, magenta and salmon modules indicated that enriched GO terms and KEGG pathways were significantly associated with metabolism, coinciding with rapid metamorphic development during these stages. For instance, the enrichment of chitin metabolic processes and chitin binding are closely related to the formation and degradation of chitin, which is a major structural component of the insect cuticle that protects insects from chemical erosion, physical abrasion and pathogenic invasion [ 53 , 54 ] and serves as an attachment matrix for other cuticular proteins, plays an important role in molting during the larval-larval and larval-pupal stages [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…To accommodate body growth during development, insect cuticle must undergo periodic moulting by replacing the old cuticle by a new one (Moussian, 2010). Moulting can be subdivided in three phases: The preparatory phase including apolysis (i.e., detachment of the old cuticle from the body surface), the cuticle induction phase when a new cuticle is formed and the ecdysial phase when the insect emerges from the old cuticle and the new cuticle maturates (Truman, 2019;Qu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…OfChtII possesses multiple CBM14 domains and GH18 domains. Here, a truncated form of OfChtII containing three CBM14 domains at the N-terminal and a GH18 domain at the C-terminal was used. , OfChi-h possesses an N-terminal fibronectin III domain and a C-terminal GH18 domain . All recombinant chitinases were secreted into the culture supernatant and were purified by a combination of ammonium sulfate precipitation and immobilized metal ion affinity chromatography (IMAC), as described previously. ,, All purified enzymes were dissolved in the sample buffer (50 mM sodium phosphate, 150 mM NaCl, pH 6.0) before use.…”
Section: Methodsmentioning
confidence: 99%
“…In chitin-containing organisms and some microbes that utilize chitin as a nutrient resource, three or more glycoside hydrolase family 18 (GH18) chitinases constitute an enzyme cocktail for chitin hydrolysis. , Synergism among the cocktail enzymes has been reported to improve hydrolytic efficiency in several bacteria, , fungi , and insects. , Current research studies suggest that the synergism attributes to the different and complementary hydrolytic pattern of GH18 chitinases . In the most well-studied systems from the bacterium Serratia marcescens, the synergy is known to take place between three GH18 chitinases, SmChiA, SmChiB, and SmChiC. ,, Both SmChiA and SmChiB are processive enzymes. , The directionality of the processive motion is linked to the architecture of the substrate-binding sites of a processive enzyme, which, through the distribution of binding energies per site, provide directionality to the (partial) dissociation and rebinding step that needs to happen in between each processive cut .…”
Section: Introductionmentioning
confidence: 99%